Status Hukum Crew Interactive Mobile Companion (CIMON) sebagai Kecerdasan Buatan dalam Misi Luar Angkasa di International Space Station (ISS) berdasarkan Hukum Ruang Angkasa - Patria Putra, Mochamad Rizcky; Handayani, Irawati (UI Scholars Hub, 2023)
Humans require assistance to support the tasks assigned to them to achieve the predetermined success in a space mission. Consequently, humans have developed artificial intelligence technology. One of the AI technologies utilized is the Crew Interactive Mobile Companion (CIMON), which results from collaboration between several space agencies and organizations, both government and private. Based on space law regulations, CIMON AI raises questions as it serves two main functions in space law: as an astronaut with a legal personality and as an object launched into space. This study aims to examine the legal status of CIMON AI in space law and analyze the safety standardization aspects of using CIMON AI on the International Space Station from the perspective of space law. It turns out that CIMON AI doesn’t have a legal personality based on corpus juris spatialis because it’s a space object whose legal responsibility is attached to the entity authorized to manage CIMON AI which now still has to increase its attention to safety standards due to inadequate legal arrangements which can ensure the implementation of activities in outer space runs according to the regulations applicable in space.